Georgia : Technical Assistance Report-Producer Price Indexes Mission. (IMF Staff Country Reports; Country Report ;, 2020)
This Technical Assistance Report paper on Georgia highlights various aspects of producer price indexes (PPI) mission. The purpose of the mission was to assist the National Statistics Office of Georgia (Geostat) with expanding the coverage of the PPI to additional services activities. Expanded PPI coverage will facilitate more accurate measurement of real output generated from services activities in Georgia. Since services activities comprised 58.4 percent of 2018 gross domestic product on a value-added basis, improved measurement in this area will significantly enhance the accuracy of total measures of the size, growth, and productivity of the Georgian economy. Improved PPIs will also provide policymakers with a clearer view of price development at the producer level, which may signal future changes in the cost of living for Georgian consumers. Geostat analysis indicated that prices for all carriers have historically changed at similar rates. This makes the consumer price index for air transportation an adequate estimator for producer prices, which should include domestic airlines only. However, PPI prices should ideally include sales to all buyer types, not just resident consumers. This makes unit value prices an attractive option. These can be calculated as total fare revenue generated from all passengers that flew in a specified class of service on all flights for a specified route, divided by this same number of passengers.